Efficacy and Mechanism of the Jiangtang Tiaozhi Recipe in the Management of Type 2 Diabetes and Dyslipidaemia: A Clinical Trial Protocol - Haoran Wu; Haoran Wu; Xinyi Fang; Xinyi Fang; De Jin; Runyu Miao; Runyu Miao; Jiahua Wei; Tianyu Zhao; Dan Dai; Dan Dai; Jiangquan Liao; et al. (Frontiers Media S.A., 2022)
Background: Type 2 diabetes mellitus (T2DM) complicated with dyslipidaemia is associated with a high risk of cardiovascular diseases. The Jiangtang Tiaozhi (JTTZ) recipe is a Chinese herbal formula that has been used to regulate the blood glucose and lipid levels for many years. Interestingly, a previous study has demonstrated its efficacy; however, the associated mechanism remains unclear. We hypothesised that the therapeutic effect of the JTTZ on patients with T2DM may be mediated by the modulation of metabolites secreted by the gut microbiota. This study aims to examine this mechanism.Methods and analysis: This study is a randomised, positive drug parallel-controlled, open-label clinical trial in patients with T2DM and dyslipidaemia. A total of 96 patients will be recruited and randomly assigned to treatment with JTTZ or metformin for 12 weeks. The primary outcome will be the rates of effectively regulated blood glucose and lipid levels (measured with the levels of glycated haemoglobin, fasting plasma glucose, 2-h plasma glucose, triglyceride, and low-density lipoprotein cholesterol). The secondary outcomes will be the changes in body weight, body mass index, and waist circumference and Traditional Chinese Medicine symptom scores. In addition, 16S rRNA gene sequencing will be performed on the gut microbiota obtained from faeces, and metabolomics analysis will be performed based on blood and gut microbiota samples. Intention-to-treat, per-protocol analysis and safety analysis will be performed.Clinical trial registration number: https://clinicaltrials.gov/ct2/show/NCT04623567